2022
DOI: 10.55493/5005.v12i3.4532
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Barley Cultivated Areas’ Actual Status in Egyptian Newly Reclaimed Lands

Abstract: Barley is a globally important strategic cereal crop, which grows well under various climatic and drought-stress conditions. In Egypt, barley is a major winter crop cultivated in old and newly reclaimed lands that suffer from a lack of irrigation, low soil fertility, and salinity of both soil and water. However, there is a lack of awareness of the nutritional role of barley for both humans and animals. Therefore, this paper aims to evaluate the actual status of cultivated areas of barley, especially in newly r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…It is a robust crop in the context of climate change. In Egypt, barley is grown in winter in both old and newly reclaimed lands that experience problems with soil fertility and salinity, and access to irrigation (El-Khalifa et al, 2022). Barley is also the most adapted field crop grown under drought and poor soil fertility in rainfed areas in Marsa Matrouh and the North Sinai.…”
Section: Indicator Crop: Barleymentioning
confidence: 99%
See 1 more Smart Citation
“…It is a robust crop in the context of climate change. In Egypt, barley is grown in winter in both old and newly reclaimed lands that experience problems with soil fertility and salinity, and access to irrigation (El-Khalifa et al, 2022). Barley is also the most adapted field crop grown under drought and poor soil fertility in rainfed areas in Marsa Matrouh and the North Sinai.…”
Section: Indicator Crop: Barleymentioning
confidence: 99%
“…Barley can be used as animal feed and for malting, but also has unique human health and nutritional benefits, including its high nutritional fibre content and beta-glucan content, which is assumed to reduce cholesterol levels (El-Khalifa et al, 2022) A functional barley seed delivery system is crucial to introduce and disseminate these varieties into the areas of their adaptation through a community-based seed production and distribution system involving farmers, research and extension services.…”
Section: Indicator Crop: Barleymentioning
confidence: 99%
“…It’s not just used as food for people and animals anymore – it’s also important for making malt, beer, and biodiesel. In 2020/2021, production was 160.53 million tons, but it fell to 147.05 million tons in 2021/2022 [ 7 , 8 ]. However, the productivity of rainfed barley in Egypt is higher than the global average productivity [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Breeding is crucial for creating toolkits of salt-tolerant crop genotypes and for implementing growth, physiological, and yield features in the field [ 33 ]. According to El-Khalifa et al [ 34 ], barley is an essential crop in Egypt and takes up 76.9% of freshly reclaimed land. Also, Mohamed et al [ 14 ] reported that, barley productivity in Egypt reached 108,000 tons in 2019 and is predicted to continue rising.…”
Section: Introductionmentioning
confidence: 99%